An 8-year retrospective review of Pyogenic Liver Abscesses at Groote Schuur Hospital, Cape Town, South Africa - Govender, Nieleshen (Division of General Surgery, 2024)
Pyogenic liver abscess (PLA) is the most common abdominal solid organ abscess with significant associated morbidity and mortality (2-30%). High variance in the causative organism exists therefore identifying the responsible pathogens and providing targeted therapy is needed for optimal outcomes. This study aims to describe patient variables, outcomes and the local microbiome to guide future empiric antibiotic protocols. Methods We performed a retrospective review of 121 patients with PLA from 2012 to 2020 at Groote Schuur Hospital. We analyzed patient demographics, microbiology results from cultures of PLA (bile, percutaneous aspiration or intra-operative sampling) and blood samples, empiric antibiotic regimens used, interventions and outcomes. Results The five most common organisms cultured were Escherichia coli [26 (21%)], Klebsiella pneumoniae [24 (19.8%)], Pseudomonas aeruginosa [12 (9.9%)], Anaerobic organisms Isolated [11 (9%)] and Enterobacter cloacae Complex [7 (5.1%)]. Twenty different regimens were used to treat PLA. Primary intervention (antibiotics alone, percutaneous drainage, open surgery) was successful in 72 patients (60%). Further intervention was required in 49 patients (40%). Open surgical drainage was required in 16 patients (13%). 30-day mortality was 9.1% (n=11). Biliary sepsis was the most common cause of PLA (31%). Our study showed Gentamicin [52 isolates (65%)], Ciprofloxacin [49 isolates (61%)] and Co-Amoxiclav [46 isolates (46%)] to be the most effective in covering the five most common isolates. Conclusion Optimal PLA management remains challenging with multiple combinations of empiric antibiotic regimens initiated. Local data on the topic is sparse and this research is hypotheses generating for future research to improve outcomes. Abstract word count: 250 words